Test Research of Low Temperature Property of Chain Material - Lu Jiguang; Wang Lili; Wei Yibo; Shao Weixian (Jixie chuandong)
The tensile tests of LH1034 leaf chains with 45 Mn plates and 35 CrMo pins are conducted under10 ℃ and- 40 ℃ temperature. The Charpy impact test of chain materials of 45 Mn,35CrMo as plate and35 CrMo,40 CrNiMoA with heat treated（ quenching and tempering process） as pin are conducted under 25 ℃ and- 40 ℃ temperature. The indoor temperature and low temperature tensile property and impact property of chain material are constract measured. The result show that the breaking load of the LH1034 plate chain under the condition of- 40 ℃ low temperature is a bit higher than 10 ℃,and the impact property of the materials under the low temperature is significantly reduced.